Mobile Health Based System for Managing and Maintaining Health Data in Classroom: Case Study - Serafimovski, Dalibor; Mitreski, Kosta; Zdravev, Zoran (UIKTEN, 2017)
It is necessary for young people to get appropriate medical education so that they can learn how to properly take care of their health from an early age. In this paper we are presenting a study that enables practical implementation of a mobile system for monitoring students’ health using mobile devices and managing medical data in the classroom. About 600 students were engaged for the purpose of this study. The study results suggest that the application of these technologies leads to an increased concern about students’ health and their proper medical education.
Keywords: mHealth, students, healthcare, smartphone, tablet, mobile devices